Obstacles to dialogue with the other: An Islamic perspective - Aldershawi, Abdullah Mohammed; Al-Salloom, Ahmed Faris; Hassan, Omar Mahmoud (Edelweiss Applied Science and Technology, 2024)
This research paper discusses the obstacles to dialogue, defining dialogue and its types while specifying its meaning in this particular study. It identifies the obstacles from the perspective of both parties involved in the dialogue. The importance of this paper lies in its examination of the obstacles from both Western and Muslim viewpoints, determining whether these obstacles are shared by both sides or unique to each. The research concludes with key findings, among which is that most of these obstacles are based on misconceptions or preconceived judgments and are not genuine obstacles. Both parties can overcome these issues.